Beliefs and Misconceptions in Pedagogical Work – Stereotypical Thinking Strategies and Reasons Behind - Hont-Gáspár, Anita; Rayman, Julianna; Szefcsik, Dóra Eperke (Autonomy and Responsibility Journal of Educational Sciences, 2022)
This study offers a summary of frequently used stereotypical thinking strategies in the Hungarian educational context. It describes eight stereotypical thinking strategies: biological racism, social reduction, performance reduction, blaming the victim, dehumanization, rationalization, exceptionalism, and colour-blindness. Beyond the illustrative theoretical summary, the aim of this study is to encourage self-refl ection of our readers by illustrating how these thinking strategies work. Citations highlighted from research interviews further support the life-likeness of the presented theories.